Multi-objective energy and exergy optimization of different configurations of hybrid earth-air heat exchanger and building integrated photovoltaic/thermal system. (1st September 2019) - Li, Z.X.; Shahsavar, Amin; Al-Rashed, Abdullah A.A.A.; Kalbasi, Rasool; Afrand, Masoud; Talebizadehsardari, Pouyan
Highlights: Energetic and exergetic analysis of two novel BIPVT-EAHE systems. Pre-heating fresh air in BIVT and EAHE and cooling the PV panels in heating mode. Pre-cooling the fresh air in EAHE and cooling the PV panels in the cooling mode. Annual total energy output of the optimum configuration A is 96448.6 kWh. Annual total energy output of the optimum configuration B is 98537.5 kWh. Abstract: Multi-objective optimization of a hybrid building integrated photovoltaic/thermal (BIPVT) system and earth-air heat exchanger (EAHE) is studied. According to the position of the BIPVT and EAHE systems, two different configurations (i.e. configuration A and configuration B) are examined. In the heating mode of the configuration A, the cold outdoor air is twice preheated by passing through the EAHE and BIPVT systems. In the cooling mode of the configuration A, the hot outdoor air is precooled by flowing inside the EAHE system and the photovoltaic (PV) modules are cooled using the building exhaust air. The cooling mode of the configuration B is similar to the configuration A, while in the heating mode of the configuration B, the outdoor air first enters the BIPVT collector and then passes through the EAHE system. The annual total amount of produced energy and exergy are considered as the objective functions. The effective parameters in the optimization process include the air mass flow rate, the length, width and depth of BIPVT channel and the length and depth of EAHE system. The outcomes revealed that the annual total energy and exergy outputs of the optimum configuration A are 96448.6 kWh and 10015.5 kWh, respectively, while these values for the optimum configuration B are respectively 98537.5 and 9888.4 kWh.